2020
DOI: 10.1016/j.neuroscience.2020.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Daily Rhythms of Lactate Metabolism in the Medial Prefrontal Cortex of Male Mice

Abstract: Aging is associated with reduced circadian (daily) rhythm amplitude in physiology and behavior, and decreased function of the prefrontal cortex (PFC). Similar effects are seen in younger mice experiencing circadian desynchrony (CD) caused by exposure to 20h light-dark cycles (T20). Given changes in PFC structure/function, underlying metabolic functioning of the PFC may also occur. We aimed to determine whether there are similarities in neurometabolism between Aged and CD mice. Using enzymatic amperometric bios… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…There is growing evidence of links between circadian rhythms and PFC function (Otsuka et al 2020; Woodruff et al 2018; Hou et al 2022; Harkness et al 2021). Previous work from our group has demonstrated that extracellular lactate (a functional output of neural metabolism) shows circadian rhythms in the medial (m) PFC, and that environmental circadian disruption alters the morphology of medial mPFC neurons and affects PFC mediated behaviors (Wallace et al 2020; Karatsoreos et al 2011). However, the studies presented here are the first to explore whether cell autonomous activity and synaptic inputs onto PFC neurons are rhythmic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence of links between circadian rhythms and PFC function (Otsuka et al 2020; Woodruff et al 2018; Hou et al 2022; Harkness et al 2021). Previous work from our group has demonstrated that extracellular lactate (a functional output of neural metabolism) shows circadian rhythms in the medial (m) PFC, and that environmental circadian disruption alters the morphology of medial mPFC neurons and affects PFC mediated behaviors (Wallace et al 2020; Karatsoreos et al 2011). However, the studies presented here are the first to explore whether cell autonomous activity and synaptic inputs onto PFC neurons are rhythmic.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of links between circadian rhythms and both PFC function and many of these neurobehavioral conditions 1, 32, 34, 42, 43 . Previous work from our group has demonstrated that extracellular lactate (a functional output of neural metabolism) shows circadian rhythms in the medial (m) PFC, and that ECD alters the morphology of medial mPFC neurons and affects PFC mediated behaviors 13, 44 . However, the studies presented here are the first to directly test whether cell autonomous activity and synaptic inputs onto PFC neurons are rhythmic, define the mechanisms by which this occurs, and investigate how circadian disruption impacts these functions.…”
Section: Discussionmentioning
confidence: 99%
“…To determine how stress-induced glutamate release is affected by chronic HPA axis disruption, mice (N = 10/group, 20 total) were implanted with printed circuit board (PCB) head stages as previously described ( Phillips et al, 2015 ; Wallace et al, 2020 ) (Pinnacle Technology, Inc., Lawrence, KS) with an additional cannula targeted to the mPFC under isoflurane anesthetic (details below). Following 7 days of recovery from surgery, mice began 4-week treatment with CORT or Vehicle solution.…”
Section: Methodsmentioning
confidence: 99%
“…For implantation of cannula and head stages for glutamate measurements described in Experiment 3 , mice were anaesthetized using 5% isoflurane in oxygen, and then maintained at 2% during the surgical procedure. Next, each mouse was prepared for electrophysiology measurements as previously described ( Phillips et al, 2015 ; Wallace et al, 2020 ). Briefly, the skull surface was exposed and four stainless steel screw electrodes (Antrin Miniature Specialties, Inc. Fallbrook, CA) were implanted, along with two screws that were implanted in the parietal lobe to anchor the head stage.…”
Section: Methodsmentioning
confidence: 99%
“…l -lactate may be closely related to aging as, in animal models, the level of this glycolytic byproduct rapidly increases in the senescent phenotype (Datta and Chakrabarti 2018 ; Wallace et al 2020 ).…”
Section: -Lactate Role In the Aging Process And The Role Of Mitochondriamentioning
confidence: 99%